Implementation of a Quality Improvement Project to Increase Access to Dietitian Services for Patients With Gastrointestinal Cancer in a Safety-Net Hospital System. Issue 7 (July 2021) - Levonyak, Nicholas S.; Hodges, Mary P.; Haaf, Nicole; Mhoon, Verca; Lopez, Ricardo; Little Jones, Amy; Sanjeevaiah, Aravind; Kainthla, Radhika; Beg, Muhammad Shaalan; Kazmi, Syed M.
Abstract : PURPOSE: Rates of malnutrition are high in patients with GI cancer, leading to poor outcomes. The aim of our project was to increase the rate of documented dietitian assessment in patients with GI cancer at Parkland Health and Hospital System from 5% to 25%. METHODS: Three PDSA cycles were conducted after identifying barriers to dietitian services. A registered dietitian was assigned to the GI oncology clinic during the first cycle, an adapted Malnutrition Screening Tool was implemented through the electronic medical record during the second cycle, and clinical staff training was performed during the third cycle. New patients with GI cancer seen by the registered dietitian had weight, Eastern Cooperative Oncology Group performance status, and serum albumin recorded at initial visit and 3-month follow-up. Paired t tests were performed. Emergency department visits and hospital admissions were also recorded during this time. RESULTS: Through these interventions, the percentage of patients with GI cancer with documented assessment by the registered dietitian increased from 5.1% in October 2018 prior to our interventions to 21.8% in July 2019 and has sustained in the 15%-20% range thereafter. From May to July 2019, there were 63 new patients with GI cancer seen by a registered dietitian. No significant difference was observed in average difference in weight and serum albumin level at initial visit and 3-month follow-up. CONCLUSION: A nutrition-focused quality improvement project led to a more than three-fold increase in the rate of documented dietitian assessment in patients with GI cancer.